Big Data Analytics and Information Science for Business and Biomedical Applications II - Ahmed, S. Ejaz; Nathoo, Farouk (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The analysis of big data in biomedical, business and financial research has drawn much attention from researchers worldwide. This collection of articles aims to provide a platform for an in-depth discussion of novel statistical methods developed for the analysis of Big Data in these areas. Both applied and theoretical contributions to these areas are showcased.